2023
DOI: 10.3390/su152316461
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Potential of AI–ML in Urban Climate Change Adaptation and Sustainable Development

Aman Srivastava,
Rajib Maity

Abstract: This study addresses a notable gap in the climate change literature by examining the potential of artificial intelligence and machine learning (AI–ML) in urban climate change adaptation and sustainable development across major global continents. While much attention has been given to mitigation strategies, this study uniquely delves into the AI–ML’s underexplored role in catalyzing climate change adaptation in contemporary and future urban centers. The research thoroughly explores diverse case studies from Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…Our findings are consistent with those of a study that used the HEC-HMS model to identify critical years marked by significant changes in each subbasin [57], unlike this study, identified important years highlighted by considerable changes in each subbasin by using the Mann-Kendall (M-K) method, sliding t-test, and cumulative anomaly test. Another study that used the LISFLOOD model, which normally models bigger areas such as river basins or continents, encountered difficulties in capturing small-scale changes in sediment transport [58].…”
Section: Runoff Variation Trendsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are consistent with those of a study that used the HEC-HMS model to identify critical years marked by significant changes in each subbasin [57], unlike this study, identified important years highlighted by considerable changes in each subbasin by using the Mann-Kendall (M-K) method, sliding t-test, and cumulative anomaly test. Another study that used the LISFLOOD model, which normally models bigger areas such as river basins or continents, encountered difficulties in capturing small-scale changes in sediment transport [58].…”
Section: Runoff Variation Trendsupporting
confidence: 90%
“…Integrating data from TN and TP variations provides for a holistic approach to nutrient management, optimizing environmental conservation efforts. Previous study [57] emphasizes the need to take a comprehensive approach to adapting to changing climatic conditions, and Similar study measures indicating a constant drop in discharge values under comparable climate change scenarios, have validated our findings [59]. However, the effects of various factors on runoff were primarily concentrated during the high-flow period of the year.…”
Section: Analysis Of Seasonal Variation Of Runoff Under Future Climat...supporting
confidence: 86%
“…Advanced machine learning (ML) techniques such as deep learning (DL) and anomaly detection are used to monitor data from various sensors and predict any potential mechanical issues [22]. This ML-based proactive monitoring helps repair/rectify mechanical issues before they escalate into major failures, which helps reduce energy consumption and emissions and increases safety [24].…”
Section: Fig 17 Social Discussionmentioning
confidence: 99%
“…Policy Initiative, are communicating the necessity of regulations in promoting A.I. use within the automotive industry [24,27]. Continued updates and governance are therefore crucial.…”
Section: Policy and Regulatory Framework For Promoting Ai/ml Adoption...mentioning
confidence: 99%